2019
DOI: 10.1002/brb3.1421
|View full text |Cite
|
Sign up to set email alerts
|

Central network changes in patients with advanced monocular blindness: A voxel‐based morphometric study

Abstract: Objective To study the changes in gray matter volume (GMV) in patients with advanced monocular blindness (MB) using voxel‐based morphometry (VBM). Methods Thirty‐one patients with advanced MB (25 males and six females) and 31 normal controls (25 males and six females) were enrolled. The t test was applied to determine the differences in GMV, white matter volume (WMV), and volume of cerebrospinal fluid in different regions of the brain. The local characteristics of spontaneous concentrations of brain tissue wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…Additionally, patients with chronic tinnitus also had abnormal ALFF value in the cingulate gyrus, which was thought to be related to psychological problems including stress, anxiety, inattention, and insomnia 37 . Similarly, previous research has also found signi cantly decreased GMV value of RACG in monocular blindness, indicating a disturbance of synchronous nerve activity in these patients 39 . A decrease in fALFF of ACG in monocular blindness further con rmed this conclusion 20 .…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, patients with chronic tinnitus also had abnormal ALFF value in the cingulate gyrus, which was thought to be related to psychological problems including stress, anxiety, inattention, and insomnia 37 . Similarly, previous research has also found signi cantly decreased GMV value of RACG in monocular blindness, indicating a disturbance of synchronous nerve activity in these patients 39 . A decrease in fALFF of ACG in monocular blindness further con rmed this conclusion 20 .…”
Section: Discussionsupporting
confidence: 76%
“…RPCG acts as the primary motor cortex and controls body movements, including eye movements. RACG and LMCG are important components of the limbic system, which play an important role in some stages of emotional processing and visual functions [35][36][37][38][39][40][41][42]. Therefore, the abnormal spontaneous brain activities we found in the above brain areas of DON patients were very meaningful findings and might partly explain the patient's symptoms and indicate the underlying neuropathological mechanism of DON.…”
Section: Discussionmentioning
confidence: 67%
“…LG is associated with visual memory 46 and FFG is involved in high‐level visual processing, such as face perception, object recognition, and reading 47 . Disrupted brain activity and reduced cortical volume of these areas indicating vison‐related dysfunctions have been reported in previous neuroimaging studies concerning amblyopia, 15,44 glaucoma, 14,48 blindness, 49 and other vision‐threatening diseases 50,51 . In TAO, Silkiss et al 3 .…”
Section: Discussionmentioning
confidence: 97%